Climate change and gendered migration patterns in Southern Africa: A review - Nzima, Divane; Maviza, Gracsious (Routledge, 2023)
In this chapter, the authors submit that embedding a gender lens has been one of the most valuable initiatives in the drive towards climate justice, emphasising social equity in climate change response strategies. Consistent with the social equity framework, they focus on how the persistent challenge of climate change continues to influence gendered migration patterns in Southern Africa and whether efforts to address this have upheld the principles of social justice. Considering the foregoing and given that most societies in Southern Africa heavily depend on rain-fed subsistence agriculture for livelihoods, and women take on the responsibility of agricultural production to provide for their families, climate change would inevitably have gendered impacts on livelihoods. Although there is limited data to prove the causal relationship, these gendered differential impacts of climate change on agro-based livelihoods may be a potential cause of the growing incidence of the increase in female migration stocks in Southern Africa.